METODE PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH SISWA - Pangestu, Dika Lita; Hidayat, Muhtar Sofwan; Muslikah, Roni (AL-QALAM: JURNAL KEPENDIDIKAN, 2022)
This study aims to determine whether the project based learning method is able to improve problem solving skills in third grade students at MIN 3 Banjarnegara. This is important for research because the problem solving ability of third grade students at MIN 3 Banjarnegara is relatively low, based on the results of initial observations it is known that the main problem is that the learning methods used by teachers are still less varied in developing these abilities. The research model used is a Classroom Action Research (CAR) research model with the model developed by Kammis and Mc. Taggart. The results of the study show that the application of the project based learning model can improve the problem solving ability of third grade students of MI N 3 Banjarnegara. The average control system engineering learning outcomes in the pre-cycle only looked for 84.85%. After using the project based learning method. In the first cycle, the average student learning outcomes increased students' problems in daily learning to 89.06% and in the second cycle increased to 95.85%. The learning average in the first cycle was 89.06% for C4 and 92.94% for C5 and in the second cycle increased to C4 95.85%, for C5 98.61%.